Belis dan Harga Seorang Perempuan Sumba (Perkawinan Adat Suku Wewewa, Sumba Barat Daya, NTT) - Kleden, Dony (Studi Budaya Nusantara, 2017)
ABSTRACTMarriage betwen man and woman, even man and man, or woman and woman, there is always talk about necessity to love one each other, and to need one each other. There for, in marriage, there are any dependence, any necessity, any reciprocity betwen man and woman, or minimal two persons. Of course, every place and culture, has uniqueness about the process or celebration of marriage. Wewewa ethnic is one of ethnic in Sumba island has uniqueness too in celebrationing marriage. Belis (bride-price) always be key of word if they want to talk about marriage. And because Belis always to be the key of marriage, feel of love sometimes not be the first of the marriage. This my short writing will be focused to many kinds of marriage in Wewewa ethnic and all games in itself. This writing based of my research few moths ago, with observation-participation approach. At the end of this writing, I will give my critical note using reciprocity theory.